2018
DOI: 10.3390/pathogens7020047
|View full text |Cite
|
Sign up to set email alerts
|

Different Dose-Dependent Modes of Action of C-Type Natriuretic Peptide on Pseudomonas aeruginosa Biofilm Formation

Abstract: We have previously shown that the C-type Natriuretic Peptide (CNP), a peptide produced by lungs, is able to impact Pseudomonas aeruginosa physiology. In the present work, the effect of CNP at different concentrations on P. aeruginosa biofilm formation was studied and the mechanisms of action of this human hormone on P. aeruginosa were deciphered. CNP was shown to inhibit dynamic biofilm formation in a dose-dependent manner without affecting the bacterial growth at any tested concentrations. The most effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The pulmonary bacteria in the context of human pulmonary health is mainly associated with respiratory diseases [20][21][22]. For example, Pseudomonas aeruginosa can cause chronic respiratory infections in the lungs [23][24][25]. Therefore, human body need to maintain an optimum level of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary bacteria in the context of human pulmonary health is mainly associated with respiratory diseases [20][21][22]. For example, Pseudomonas aeruginosa can cause chronic respiratory infections in the lungs [23][24][25]. Therefore, human body need to maintain an optimum level of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, whereas hBNP and hCNP have no impact at 1 and 0.1 µM on P. aeruginosa growth [37, 68], bacterial exposure to these peptides at 1 µM stimulates the virulence of P. aeruginosa and P. fluorescens [37, 38]. In addition, both hBNP and hCNP at 0.1 µM strongly prevented P. aeruginosa biofilm formation [69].…”
Section: Effects Of Peptidic Hormones On Gram-negative Bacteriamentioning
confidence: 99%
“…In addition, both hBNP and hCNP at 0.1 µM strongly prevented P. aeruginosa biofilm formation [69]. The most active peptide was hCNP, which was able to impair biofilm formation in a dose-dependent manner, and which was still able at 10 nM to reduce by a half the biofilm formation by P. aeruginosa [68]. …”
Section: Effects Of Peptidic Hormones On Gram-negative Bacteriamentioning
confidence: 99%
See 2 more Smart Citations